Panel Data Model in Analyzing Factors Affecting Market Value Added (MVA) in Companies Listed on the LQ45 Index - Ardana, Yudhistira; Syamsiyah, Nur; Faiz, Akhmad (Universitas Negeri Yogyakarta, 2023)
ABSTRACTTo increase shareholder value, companies are required to improve their financial performance. MVA (Market Value Added) is one of the company's performance indicators for increasing MVA. This study aims to measure the factors that affect the market value added (MVA) of companies listed on the LQ45 index using a panel data model. The variables used are economic value added (X1), return on equity (X2), return on assets (X3), earnings per share (X4), dividend per share (X5), and market value added (Y). The best model used in this study is the random-effects model. The estimation results show that all variables used in this study (EVA, ROA, ROE, EPS, and DPS) have a significant effect on the MVA of companies incorporated in the LQ45 index, with a percentage of 64.68%. The results of the partial estimation of the ROA, ROE, and EVA variables have a significant positive effect on MVA. The DPS variable has no significant positive impact on MVA, and the EPS variable has no significant negative impact on MVA.Keywords: Economic Value Added, Profitability Ratio, Market Value AddedABSTRAKUntuk meningkatkan nilai pemegang saham, perusahaan dituntut dalam meningkatkan kinerja keuangannya. Market Value Added (MVA) merupakan salah satu indikator kinerja perusahaan dalam meningkatkan nilai tambah pasar. Penelitian ini bertujuan untuk mengukur faktor-faktor yang mempengaruhi Market Value Added (MVA) perusahaan yang terdaftar pada indeks LQ45 dengan menggunakan model data panel. Variabel yang digunakan adalah Economic Value Added (X1), Return on Equity (X2), Return on Asset (X3), Earning Per Share (X4), Dividend Per Share (X5), dan Market Value Added (Y). Model terbaik yang digunakan dalam penelitian ini adalah model random-effect. Hasil estimasi menunjukkan bahwa semua variabel yang digunakan dalam penelitian ini (EVA, ROA, ROE, EPS, dan DPS) berpengaruh signifikan terhadap MVA perusahaan yang tergabung dalam indeks LQ45 dengan persentase 64,68%. Hasil estimasi parsial variabel ROA, ROE, dan EVA berpengaruh positif signifikan terhadap MVA. Variabel DPS berpengaruh positif tidak signifikan terhadap MVA dan variabel EPS berpengaruh negatif tidak signifikan terhadap MVA.Kata Kunci: Nilai Tambah Ekonomi, Rasio Profitabilitas, Nilai Tambah Pasar